The content of a dental mobile application for children from the perspectives of parents and pre-school teacher trainees - KİTAPÇI, OKAN CEM; AKMANSOY, ŞÜKRÜ CAN; ŞİŞMAN KİTAPÇI, NUR; MUMCU, GONCA (My University, 2023)
Objective: The aim of this study was to describe the most desirable content of a dental application (dental app) for children from the perspectives of parents and preschool teacher trainees.Materials and methods: In this cross-sectional study, 51 parents whose children (36-72 months) were students in a preschool educational institution and 99 preschool teacher trainees in the same institution were included. Data were collected by the structured questionnaire in the face-to-face interviews regarding the desirable content of the dental app. The ratios of 1st ranked of the most prominent content and videos were noted.Results: In the study, \"List of institutions for oral and dental health services\" and \"Importance of regular dental examinations\" were observed to be important items for both (21,6%) and teacher trainees (24,2% and 19,2%) according to the scores of 1st ranked contents in a dental app. Moreover, the item \"Funny and educational games containing oral health\" for the video theme were 1st ranked item in the one-third of the parents (33,3 %).Conclusion: In a dental app, list of dental services was the prominent item for both parents and preschool teacher trainees. Moreover, the use of educational and entertaining videos may help the improvement of children’s oral health for them.

Amaç: Bu çalışmanın amacı, ebeveynler ve okul öncesi öğretmen adaylarının bakış açılarından çocuklar için bir diş hekimliği uygulamasında en çok istenen içeriği tanımlamaktır. Gereç ve Yöntemler: Kesitsel tipte tanımlayıcı araştırmaya, çocukları (36-72 aylık) bir okul öncesi eğitim kurumunda öğrenci olan 51 ebeveyn ve aynı kurumdaki 99 okul öncesi öğretmen adayı dahil edilmiştir. Veriler, dental uygulamanın istenen içeriğine ilişkin yapılandırılmış anket formuyla yüz yüze görüşmelerle toplanmıştır. İçerik ve videolar için 1. sıradaki puanlama oranları dikkate alınmıştır. Bulgular: Ağız ve diş sağlığı mobil uygulamasında istenilen içerikler için hem ebeveynlerin (%21,6) hem de okul öncesi öğretmen adaylarının (%24,2 ve %19,2) “Ağız ve diş sağlığı hizmeti almak için başvurulabilecek kurumların listesi” ve “Düzenli diş hekimi muayenesinin önemi” maddelerini öncelikli olarak belirttiği görülmüştür. Ayrıca, video temasındaki “Oral sağlığa yönelik eğlenceli ve eğitici oyunlar” maddesi ebeveynlerin (%33,3) üçte biri tarafından 1.sırada belirtilmiştir. Sonuç: Ebeveynler ve okul öncesi öğretmen adayları perspektifinde, çocuklara yönelik dişhekimliği mobil uygulamalarında ağız ve diş sağlığı hizmeti veren kurumlar listesinin yer alması önerisi öne çıkan madde olmuştur. Ayrıca, eğitici ve eğlenceli videoların kullanılmasının çocukların oral sağlığının geliştirilmesine yardımcı olabileceği düşünülmüştür
Ebeveynlerin ve okul öncesi öğretmen adaylarının gözünden çocuklara yönelik diş mobil uygulaması içeriği
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Oral Sağlık; çocuklar; ebeveynler; okul öncesi öğretmen adayları; dental aplikasyon.; Oral health; children; parents; preschool teacher trainees; dental app